2015
DOI: 10.1142/s2010007815500116
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Forest in an Integrated Assessment Model of the Climate and the Economy

Abstract: This paper develops the FOR-DICE model to explore the potential role of the global forest in reducing climate change. It presents a basic framework for assessing the boreal, tropical, and temperate forests as both a source of renewable energy and a resource to sequester and store carbon. The focus of the paper is to explore whether climate policies should focus on increasing the forest biomass, to sequester and store carbon, or on increasing the use of the forest biomass as a source of energy, to substitute fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…1 A detailed explanation of the choice between general and partial equilibrium models is given, e. g. by Eriksson (2015).…”
Section: Model Designmentioning
confidence: 99%
“…1 A detailed explanation of the choice between general and partial equilibrium models is given, e. g. by Eriksson (2015).…”
Section: Model Designmentioning
confidence: 99%
“…This paper uses a version of the FOR-DICE model by Eriksson (2015). The FOR-DICE model is an extension of the DICE-2007(Nordhaus, 2008.…”
Section: The Integrated Assessment Modelmentioning
confidence: 99%
“…The reader is referred to Eriksson (2015) for further details on the model. The model has three types of forest stocks: tropical forest, temperate forest, and boreal forest.…”
Section: The Integrated Assessment Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen fertilization with higher stocking increased the climate impacts further (Paper I), but using up to 20% higher stocking and an earlier final felling may be the best option to increase both the climate impacts and economic returns, compared to the baseline (Papers I, III). Previously, it has been suggested that cost-effective climate benefits of forest biomass could be generated by increasing the growing stock of forests (Richards and Stokes 2004;Eriksson 2015;Vass and Elofsson 2016).…”
Section: Climate Impacts Of Biomass Production and Utilizationmentioning
confidence: 99%